Evaluation of the quality Management in the Food and Nutrition Unit: feasibility study (Research, Society and Development, 2021)
The study aimed to evaluate the hygienic-sanitary and structural conditions of a Food and Nutrition Unit, proposing the development of strategies for the implementation of quality management programs. Exploratory study, with a qualitative and quantitative approach to data, addressing a food and nutrition service. For the assessment of hygienic-sanitary conditions, daily and weekly checklists were used. Regarding the results, low overall scores and high frequencies of unsatisfactory conditions were observed in part of the evaluated sectors. The sectors of pans and pre-preparation of salads with the highest non-compliance items and the cleaning of trays and utensils sector with the highest score in terms of compliance were identified. In view of the results found, it is clear that the Food and Nutrition Unit presented unfavorable hygienic-sanitary conditions, a fact that can compromise the safety of food prepared in these places. The follow-up of good practices and compliance with them by the Food and Nutrition Unit is essential for the production of safe foods that contribute to the health and well-being of diners.